An Investigation into Hufi English-Majored Students’ Issues with Translation and Interpretation - Hien, Nguyen Thanh (Journal of English Language Teaching and Applied Linguistics, 2021)
English Language programs that seek to offer learners adequate English skills and translate strategies to conduct in multilingual environments include translation and interpretation. However, translating effectively is not a simple task because English language skills are not the only factor to consider; other factors also play a role. Owing to their poor language proficiency and comprehension of translation methods, many HUFI English-majored students have no experience with translation and interpretation. Therefore, this paper looked at how HUFI English-majored students approach translation and interpretation tasks and how successful those translated versions are in relation to the original Vietnamese documents. The results showed many incorrect translated items caused by “word-by-word” translation or meta-phrase technique and the influence of the Vietnamese language on two translated texts and talks from ten participants. Teachers of translation and interpretation subjects and students will get advice on improving the curriculum and teaching methods.